Strategi Komunikasi Digitalisasi Ganjar Pranowo Menuju Pilpres 2024 - Muhammad Habibi Putra Pratama; Erwan Efendi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
This research aims to determine the digitalization communication strategy of Ganjar Pranowo as the 2024 presidential candidate during the campaign. The focus is on utilizing social media as a political tool to increase Ganjar Pranowo's electability as a presidential candidate. This research was carried out with a qualitative approach, because this qualitative research leads to the interpretation of the phenomena that occur, namely the researcher as the key instrument. Content analysis techniques were applied in this research to understand each of Ganjar Pranowo's digitalization communication strategies in the form of uploading content on social media. The data collection technique uses primary data collected through observation on social media, and secondary data obtained through documentation. The research results show that Ganjar Pranowo is taking advantage of digitalization to increase his electability in the 2024 presidential election. With content that is widely distributed on social media, Ganjar is trying to build strong communication with the public. However, until the end of the campaign, Ganjar was unable to increase his eligibility because the public stigma attached to him caused their trust to slowly recede in the figure of Ganjar who was proposed as a presidential candidate in 2024.